Penyelesaian Sengketa Kesehatan Dengan Metode Non Litigasi, Mediasi, Arbitrase Dan Alternatif Lainnya - Maryanto; Irwan Triadi (Journal of Law Perspectives Review, 2025)
This article aims to analyze the effectiveness of non-litigation dispute resolution methods in the healthcare sector, focusing on mediation, arbitration, and other alternatives such as negotiation, conciliation, and expert determination. This study employs a qualitative approach through normative legal analysis and literature review of relevant Indonesian laws and regulations, including Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, the Medical Practice Law, and Supreme Court Regulation No. 1 of 2016 on Mediation Procedures. The findings indicate that non-litigation methods offer significant advantages over traditional litigation, particularly in terms of time efficiency, cost reduction, and the preservation of relationships between patients and healthcare providers. Mediation facilitates mutually beneficial agreements (win-win solutions), while arbitration provides binding decisions without lengthy court procedures. Additionally, internal complaint mechanisms and the roles of institutions such as the Indonesian Medical Disciplinary Honorary Council (MKDKI) contribute to the institutionalization of non-litigation approaches. In conclusion, non-litigation healthcare dispute resolution is a more adaptive, humane, and trust-based solution that aligns with the demands of responsive healthcare services. Enhancing legal literacy and institutional capacity in mediation practices is essential to broaden the implementation of these methods.